International Conference on Biomedical and Intelligent Systems (IC-BIS 2022) 2022
DOI: 10.1117/12.2660582
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of drought tolerant flax varieties based on genome-wide SNP

Abstract: To clarify the genetic diversity among typical drought tolerant flax varieties, in this study, the Single-nucleotide polymorphism sites (SNPs) of 29 drought tolerant flax varieties were identified by whole-genome resequencing, and their SNP characteristics and genetic relationships were analyzed. The results showed that 1069106 SNP sites were obtained from the genome of the 29 drought tolerant flax varieties, among which the variety with the largest number of SNP was Zhangya 2 (1027658) and the least was Shach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…In our previous studies, we confirmed that there is a wide genetic diversity in the genomes of different varieties of flax, which is influenced by many factors, such as parental and geographical origin [37]. In this study, we confirmed that the distribution of DEGs in the MYB family of different flax varieties is also significantly different under drought stress (Table 1, Figure 1).…”
Section: The Distribution Of Degs In the Myb Family Of 20 Flax Variet...supporting
confidence: 81%
See 1 more Smart Citation
“…In our previous studies, we confirmed that there is a wide genetic diversity in the genomes of different varieties of flax, which is influenced by many factors, such as parental and geographical origin [37]. In this study, we confirmed that the distribution of DEGs in the MYB family of different flax varieties is also significantly different under drought stress (Table 1, Figure 1).…”
Section: The Distribution Of Degs In the Myb Family Of 20 Flax Variet...supporting
confidence: 81%
“…Based on previous research, such as the identification and cluster analysis of drought resistance in early field experiments, combined with the recommendations of drought-resistant varieties from the national oil crop industry technical system, 18 drought-resistant flax varieties and two water-sensitive varieties as control varieties were screened in this study to conduct the drought stress test ( Table 4 , Supplementary Table S4 ) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%